Cancer and dementia: an exploratory study of the experience of cancer treatment in people with dementia. Issue 9 (9th August 2016) - Courtier, Nick; Milton, Rebecca; King, Amanda; Tope, Rosie; Morgan, Susan; Hopkinson, Jane
Abstract: Objective: Patients with comorbid cancer and dementia have poorer outcomes than those without dementia. We observe oncology teams managing patients with dementia and memory loss and explore these patients' needs and experiences of outpatient cancer services. Methods: A single site investigation of case study design to examine practices in four clinics using multi‐methods of data collection: retrospective note review, observation, interviews, and recorded consultations. A framework analytic approach identifies themes within and across cases. Results: Thirty‐three clinical encounters with patients with memory loss were observed. Ten consultations were audio‐recorded and 16 individuals interviewed (n = 6 patients‐carer dyads, n = 1 lone patient, and n = 5 staff). Medical records were reviewed for 338 cases. Cancer referrals did not document memory health, so clinicians rely on patient/carer disclosure to identify patients with memory problems. In practice, the problem often remains hidden. Treating teams who do become aware of memory difficulties are unsure how to support patients, but marked memory loss can limit treatment options and preclude radical intent. Carers are key facilitators of successful cancer consultations and management. Their support needs are largely unrecognized. Conclusions: Training that educates cancer teams on how to identify and support individuals with memory problems before and during treatment and recognize the carer role may facilitate complex cancer care and help reduce inequalities of outcomes.